Social Interaction at the End of the Pre-Pottery Neolithic B: an Inter-site Analysis in the Euphrates Valley. Issue 2 (2nd July 2014) - Borrell, Ferran; Molist, Miquel
Abstract : This article discusses contact, social relationships, and social organization between sites at the end of the Pre-Pottery Neolithic in the Euphrates valley; all of which are of high importance for reconstructing and modelling social organization in consolidated agricultural villages. Our analysis has succeeded in identifying a complex range of overlapping levels and types of social interaction that occurred simultaneously and operated at different scales including the household, the community and inter-regional communities. This complex mixture of interacting spheres, together with the identification of cultural-social boundaries, enables us to understand and explain inter-site variation in material culture and mortuary practices. Moreover, they reflect the growing social complexity of large farming communities at the end of the Pre-Pottery Neolithic and the role played by settlement as the social unit through which these communities became more distinctive and self-consciously different.